A cinnamyl alcohol dehydrogenase–like scaffold organizes monoterpenoid indole alkaloid biosynthesis - Di Gao; Scott Galeung Alexander Mann; Binbin Chen; Yuanwei Gou; Cong Chen; Chong Qiao; Jorge Jonathan Oswaldo Garza-Garcia; Mohammadamin Shahsavarani; Xiaojing Jiang; Hannah Caroline Tran; Jingfei Bao; Mathew Bailey Richardson; et al. (Science, 2026)
Biosynthesis of ~3,000 monoterpenoid indole alkaloids (MIAs), including the anticancer drug vinblastine, involves the highly unstable intermediate strictosidine aglycone. Its formation by strictosidine β-glucosidase (SGD) and subsequent conversion by geissoschizine synthase (GS) occur in spatially separated compartments, representing a major biosynthesis bottleneck. Here we discover VinBLAST, a cinnamyl alcohol dehydrogenase–like protein repurposed as a scaffold for efficient processing of this labile intermediate. VinBLAST physically mediates SGD and GS interaction in the nucleus and allosterically enhances GS catalytic efficiency. VinBLAST homologs from diverse plant families enhance biosynthesis of several representative MIAs, with the production of catharanthine increased to ~160 mg L −1 in yeast, nearly 1,000-fold higher than previous studies. Our discovery provides a missing link in organizing MIA biosynthesis and enables scalable bioproduction of geissoschizine-derived therapeutics.